Mezőgazdasági társas vállalkozások vizsgálata a KSH Cég-Kód-Tár adatbázisa alapján - Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The enterprises which are involved in agriculture as their main activity represent about 1.7 percent of the Hungarian enterprises. Most of the food industry enterprises can be found in the Southern Great Plain Region, the Northern Great Plain and in Central Hungary (including the capital city). The most popular form of operation is the limited liability company (62%) and the limited partnership (25%). Nearly 90% can be considered as micro or small-sized companies, 55 percent has an annual income under 20 million HUF (-70.0006), 83 percent of the companies operate with less than 10 employees. Most of the firms are involved in growing of cereals (except rice), leguminous crops and oil seeds: support activities for crop production; raising of poultry; growing of vegetables and melons, roots and tubers; raising of swin^pigs; growing of pome fruits and stone fruits; raising of dairy cattle and support activities for animal production. By calculating association coefficients, moderate connection was found between the place of headquarter and the form of operation, the main activity. There was a little bit weaker connection detectable between the place of headquarter and the number of employees or the annual income.